Effect of Praener in the Contextual Teaching and Learning Model on the Sciences Learning Outcomes of Elementary School Students - Mely Rohmawati; Yuni Ratnasari; Sekar Dwi Ardianti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Science education at the elementary school level requires a connection between students' direct experiences and scientific concepts in order to create meaningful understanding. Although the Contextual Teaching and Learning (CTL) model has been widely implemented to improve learning outcomes, most studies still focus on the core stage of learning and do not clearly emphasize strengthening the early phase as a systematic strategy to prepare students' cognition. This gap is the background for this study, which aims to evaluate the novelty of Praener (energy practices) as reinforcement of the early phase in the CTL model to build initial schemas and conceptual bridges before the implementation of core learning. This study aims to analyze the use of Praener in the CTL model on the science learning outcomes of third-grade students regarding the introduction to energy forms. The method used was a quantitative approach with a one-group pretest-posttest pre-experimental design involving 23 third-grade students at SD 4 Gondangmanis in the 2025/2026 academic year. Data were collected through tests, observations, interviews, and documentation, then analyzed using a paired sample t-test and N-Gain test. The results of the study showed a significant difference between the pretest and posttest scores, with an average increase from 48.95 to 83.65 and an N-Gain score of 0.6948, which is classified as moderate (quite effective). This improvement occurred evenly across cognitive levels C1 to C6 and was particularly high in process skills. These findings confirm that Praener is effective in strengthening cognitive readiness and have practical implications for teachers, who can systematically integrate early experiences into CTL learning to make it more contextual and meaningful.